(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This scientific article provides extensive information on the impact of environmental pollution on human health. Environmental pollution has existed since the beginning of life, resulting in the generation of waste. Managing and recycling waste in air, water, soil, and noise pollution are key principles in combating environmental pollution and contributing to the improvement of human health.